CPAP Therapy of Obstructive Sleep Apnea in Type 2 Diabetics Improves Glycemic Control During Sleep - Dawson, Arthur (American Academy of Sleep Medicine, 2008)
BACKGROUND: Type 2 diabetes and obstructive sleep apnea (OSA) are frequently comorbid conditions. OSA is associated with increased insulin resistance, but studies of continuous positive airway pressure (CPAP) have shown inconsistent effects on glycemic control. However, endpoints such as hemoglobin A1c and insulin sensitivity might not reflect short-term changes in glycemic control during sleep. METHODS: We used a continuous glucose-monitoring system to measure interstitial glucose every 5 minutes during polysomnography in 20 patients with type 2 diabetes and newly diagnosed OSA. The measurements were repeated after an average of 41 days of CPAP (range 26–96 days). All patients were on a stable diet and medications. Each 30-second epoch of the polysomnogram was matched with a continuous glucose-monitoring system reading, and the sleeping glucose level was calculated as the average for all epochs scored as sleeping. RESULTS: The mean sleeping glucose decreased from untreated (122.0 ± 61.7 mg/dL) to treated (102.9 ± 39.4 mg/dL; p = 0.03 by Wilcoxon paired rank test). The sleeping glucose was more stable after treatment, with the median SD decreasing from 20.0 to 13.0 mg/dL (p = 0.005) and the mean difference between maximum and minimum values decreasing from 88 to 57 mg/dL (p = 0.003). The change in the mean hemoglobin A1c from 7.1% to 7.2% was not significant. CONCLUSIONS: Our study is limited by the lack of a control group, but the results suggest that sleeping glucose levels decrease and are more stable after patients with type 2 diabetes and OSA are treated with CPAP. CITATION: Dawson A; Abel SL; Loving RT; Dailey G; Shadan FF; Cronin JW; Kripke DF; Kline LE. CPAP therapy of obstructive sleep apnea in type 2 diabetics improves glycemic control during sleep. J Clin Sleep Med 2008;4(6):538–542.